Assessing Years of Life Lost Versus Number of Deaths in the United States, 1995–2015 - Taksler, Glen B. (Am J Public Health, 2017)
Objectives. To assess years of life lost to each cause of death in the United States between 1995 and 2015, and compare it with the number of deaths. Methods. We used Vital Statistics mortality data and defined “life-years lost” as remaining life expectancy for each decedent’s age, sex, and race. We calculated the share of life-years lost to each cause of death in each year, and examined reasons for changes. Results. In 2015, heart disease caused the most deaths, but cancer caused 23% more life-years lost. Life-years lost to heart disease declined 6% since 1995, whereas life-years lost to cancer increased 16%. The increase for cancer was entirely attributable to population growth and longer life expectancy; had these factors remained constant, life-years lost to heart disease and cancer would have fallen 56% and 38%, respectively. Accidents (including overdoses), suicides, and homicides each caused twice the share of life-years lost as deaths. Measuring life-years lost highlighted racial disparities in heart disease, homicides, and perinatal conditions. Conclusions. Life-years lost may provide additional context for understanding long-term mortality trends.